The Role of National Parks in Promoting Sustainable and Responsible Tourism - Joanna Szczęsna; Paweł Wojtanowicz (Barometr Regionalny)
One of the contemporary challenges in the tourism industry is development in line with the idea of sustainable development. In order to implement these ideas and principles, broadly based social education is needed. National parks are institutions of great socio-educational impact and that is why they could be linked to the process of education for sustainable and responsible tourism. This article presents the results of a survey conducted in Polish national parks on their commitment to the process of social education promoting sustainable and responsible tourism, and indicates the still unused potential of national park activities which can contribute to raising public awareness in this regard.